Performance of a Multianalyte 'Rule-Out' Assay in Pregnant Individuals With Suspected Preeclampsia. Issue 7 (12th May 2022) - Costantine, Maged M.; Sibai, Baha; Bombard, Allan T.; Sarno, Mark; West, Holly; Haas, David M.; Tita, Alan T.; Paidas, Michael J.; Clark, Erin A.S.; Boggess, Kim; Grotegut, Chad; Grobman, William; et al.
Abstract : Background: The ability to diagnose preeclampsia clinically is suboptimal. Our objective was to validate a novel multianalyte assay and characterize its performance, when intended for use as an aid to rule-out preeclampsia. Methods: Prospective, multicenter cohort study of pregnant individuals presenting between 28 0/7 and 36 6/7 weeks' with preeclampsia-associated signs and symptoms. Individuals not diagnosed with preeclampsia after baseline evaluation were enrolled in the study cohort, with those who later developed preeclampsia, classified as cases and compared with a negative control group who did not develop preeclampsia. Individuals with assay values at time of enrollment ≥0.0325, determined using a previously developed algorithm, considered at risk. The primary analysis was the time to develop preeclampsia assessed using a multivariate Cox regression model. Results: One thousand thirty-six pregnant individuals were enrolled in the study cohort with an incidence of preeclampsia of 30.3% (27.6%–33.2%). The time to develop preeclampsia was shorter for those with an at-risk compared with negative assay result (log-rank P <0.0001; adjusted hazard ratio of 4.81 [3.69–6.27, P <0.0001]). The performance metrics for the assay to rule-out preeclampsia within 7 days of enrollment showed a sensitivity 76.4% (67.5%–83.5%), negative predictive value 95.0% (92.8%–96.6%), and negative likelihood ratio 0.46 (0.32–0.65). Assay performance improved if delivery occurred <37 weeks and for individuals enrolled between 28 and 35 weeks. Conclusions: We confirmed that a novel multianalyte assay was associated with the time to develop preeclampsia and has a moderate sensitivity and negative likelihood ratio but high negative predictive value when assessed as an aid to rule out preeclampsia within 7 days of enrollment. Registration: The study was registered on Clinicaltrials.gov (Identifier NCT02780414).